The influence of environmental conditions on the feed consumption, animal performance and behaviour of charolais-ayrshire cross-bred suckler cows - Huhta, Harri; Manninen, Merja; Virkajärvi, Perttu; Kaustell, Kaisa; Aspila, Pentti (1996)
v ok